Testing Cancer Immunotherapy in a Human Immune System Mouse Model: Correlating Treatment Responses to Human Chimerism, Therapeutic Variables and Immune Cell Phenotypes - Marín-Jiménez, Juan A.; Capasso, Anna; Lewis, Matthew S.; Bagby, Stacey M.; Hartman, Sarah J.; Shulman, Jeremy; Navarro, Natalie M.; Yu, Hui; Rivard, Chris J.; Wang, Xiaoguang; Barkow, Jessica C.; Geng, Degui; et al. (Frontiers in Immunology, 2021)
Over the past decade, immunotherapies have revolutionized the treatment of cancer. Although the success of immunotherapy is remarkable, it is still limited to a subset of patients. More than 1500 clinical trials are currently ongoing with a goal of improving the efficacy of immunotherapy through co-administration of other agents. Preclinical, small-animal models are strongly desired to increase the pace of scientific discovery, while reducing the cost of combination drug testing in humans. Human immune system (HIS) mice are highly immune-deficient mouse recipients reconstituted with human hematopoietic stem cells. These HIS-mice are capable of growing human tumor cell lines and patient-derived tumor xenografts. This model allows rapid testing of multiple, immune-related therapeutics for tumors originating from unique clinical samples. Using a cord blood-derived HIS-BALB/c-Rag2nullIl2rγnullSIRPαNOD (BRGS) mouse model, we summarize our experiments testing immune checkpoint blockade combinations in these mice bearing a variety of human tumors, including breast, colorectal, pancreatic, lung, adrenocortical, melanoma and hematological malignancies. We present in-depth characterization of the kinetics and subsets of the HIS in lymph and non-lymph organs and relate these to protocol development and immune-related treatment responses. Furthermore, we compare the phenotype of the HIS in lymph tissues and tumors. We show that the immunotype and amount of tumor infiltrating leukocytes are widely-variable and that this phenotype is tumor-dependent in the HIS-BRGS model. We further present flow cytometric analyses of immune cell subsets, activation state, cytokine production and inhibitory receptor expression in peripheral lymph organs and tumors. We show that responding tumors bear human infiltrating T cells with a more inflammatory signature compared to non-responding tumors, similar to reports of “responding” patients in human immunotherapy clinical trials. Collectively these data support the use of HIS mice as a preclinical model to test combination immunotherapies for human cancers, if careful attention is taken to both protocol details and data analysis.